REPRESENTASI PEREMPUAN BERAMBUT PIRANG DALAM BLONDE JOKES - Sya’baningrum Prihhartini (Fakultas Komunikasi, Sastra, dan Bahasa, 2014)
This paper is about how blonde women are represented in blonde jokes. Throughout times, blondes are portrayed in two stereotypes: a) they are described as physically and sexually attractive, and b) they are described as brainless, su-perficial, and use looks over brain. The latter description is especially exploited through Blonde jokes. Blonde jokes tend to ridicule women by exposing how unin-telligent they are. This paper then tries to: a) uncover the structure of text of blonde jokes to see how blondes are represented, and in relation with general perception about blondes, b) see how stereotype is built in society. Norman Fairclough’s critical discourse analysis theory will be used to see the relation be-tween text, interpretation, and context. J.M. Suls’s two stage model of infor-mation-processing analysis in jokes will be used to discover the structure of the jokes, and Stuart Hall’s representation theory will be used to see how stereotype is built in society.